PRODUCTION OF RECOMBINANT ANTIGEN OF BRUCELLA – CU-ZN-SOD - Shustov, A.V.; Yeskendirova, S.Z.; Manat, E.; Unysheva, G.B.; Sarina, N.I . (Eurasian Journal of Applied Biotechnology, 2013)
Periplasmic protein Cu-Zn-SOD (superoxide dismutase) is one of the major antioxidant enzymes of microorganisms, which is regarded as one of the universal mechanisms of the pathogenesis of infectious diseases, and indicators reflecting changes in the levels of antioxidant enzymes are key factors contributing to predict disease outcome. Therefore, Cu-Zn-SOD, being in the periplasm of Brucella, protects the membrane and periplasmic structure from the impact of exogenous superoxide and is one of the factors of pathogenicity. In this study, we defined immunogenicity of candidate protein of brucellosis causative agent and GenBank NCBI database was used for choosing a good expression system for diagnostic purposes candidate antigen. The gene design of Cu/Zn superoxide dismutase was in silico built. The first oligonukelotids design confirmed for constuction of wholе gene of SOD which expressing in E.coli, and codon modification was stabilized. Solid phase method was used for the synthesis of the target gene SOD de novo by automated DNA synthesizer. The gene of SOD was synthesized by PCR. The second round PCR product length was 496 bp. Then the PCR product cloned into no exprssion pB32 plasmid. Recombinant proteins C-terminus consists of six histidine (His) residues and N- terminus consists useful amino acid motif and they are used for affinity purification of polyhistidine-tagged recombinant proteins expressed in E.coli by pET22b+ plasmid. Then the pET22b+/SOD transformed into E.coli BL21(DE3), and expression of recombinant protein was estimated.